PENINGKATAN KREATIFITAS MELALUI PERMAINAN KARTU GAMBAR ANAK USIA 3-4 TAHUN PADA KELOMPOK BERMAIN UPINIPIN KOTA MAKASSAR - Andi Besse Marda (AIJER: Algazali International Journal Of Educational Research, 2019)
Abstract: Increasing Creativity through Card Game Pictures 3-4 Years Old Children in Makassar City at Upinipin Play Group. The purpose of this research was to increase creativity through the image card media in early childhood UpinIpin Makassar City Play Group (KB). This type of research was classroom action research (CAR). The location of this research was Play Group (KB) UpinIpin Makassar City Academic Year 2018/2019. Classroom action research was conducted in January - February 2019 Academic Year 2018/2019. The subjects of this classroom action research were students aged 3-4 years with 12 children. The instrument used in this study was the observation sheet and documentation. The results of data analysis obtained by the findings of the image card media usage applied in PAUD Upinipin could improve the ability to recognize images and provide excellent results for the development of children's abilities. Before playing the picture card game, the children was able to recognize the picture of only 45.3%, after the intervention using picture card game in the process of playing the children obtained the results in the first cycle reached 53% and the second cycle increased to 77%. Children creativity can be improved through the application of 3-4 year old picture card games in the Upinipin Play Group Makassar City.